Prevalence and characteristics of bladder wall thickening in dogs without lower urinary tract disease: an ultrasonographic study - François, Chloé; Billen, Frédéric; Noël, Stéphanie; Etienne, Anne-Laure; Seidel, Laurence; Bolen, Géraldine (Frontiers in Veterinary Science, 2025)
IntroductionAssessment of bladder wall thickness by ultrasound is influenced by bladder distension and body weight, complicating interpretation. In the author’s experience, cranial or cranio-ventral bladder wall thickening is commonly observed in dogs without lower urinary tract disease. One of our main hypotheses is that this thickening reflects physiological mucosal folding, which becomes more pronounced as bladder distension decreases. However, bladder thickening remains poorly documented in healthy dogs. This study aimed to investigate the prevalence and characteristics of bladder wall thickening in dogs without lower urinary tract disease.MethodsMedical data of 136 dogs without lower urinary tract disease signs, undergoing abdominal ultrasound and urinalysis, were retrospectively reviewed. Ultrasound data included bladder wall thickening presence and localization (cranial, ventral, cranio-ventral, …, generalized), aspect of the luminal surface (smooth-irregular) and the urine, and bladder distension (empty, mild, moderate, severe). A wall thickness ratio (maximum/minimum thickness) was calculated in cases of asymmetrical thickness. Multivariate logistic regression (p < 0.05) assessed associations between bladder wall thickening and other medical and ultrasound data.ResultsBladder wall thickening was observed in 42.6% of cases, predominantly in the cranio-ventral region (22.1%), followed by the cranial (11%), generalized (8%), and ventral (5%) regions. Thickening was more frequent in mildly (29.4%) and moderately (10.3%) distended bladders. Significant associations were found between thickening and age (OR = 1.16), gastrointestinal (OR = 5.49), and renal diseases (OR = 5.57). Sterilized dogs were less likely to exhibit cranio-ventral thickening (OR = 0.36). The median thickness ratio was not statistically significant across bladder sizes (p = 0.82): 2.0 for mildly, 1.95 for moderately, and 1.9 for severely distended bladder.ConclusionThese findings suggest that mild cranio-ventral/cranial bladder thickening is common in dogs without lower urinary tract disease with a median thickness ratio ≤ 2.0 and should not be confound with cystitis.